2005
DOI: 10.1002/j.1551-8833.2005.tb07451.x
|View full text |Cite
|
Sign up to set email alerts
|

Lead leaching from inline brass devices: A critical evaluation of the existing standard

Abstract: The American National Standards Institute/NSF Standard 61, Section 8, is intended to protect the public from inline brass plumbing products that might leach excessive levels of lead to potable water. Experiments were conducted to examine the practical rigor of this test. Contrary to expectations, the test was not highly protective of public health. In fact, results indicated that small devices made of pure lead—which pose an obvious public hazard—can easily pass the leaching protocol. Reforms are needed to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Hu et al (2006) observed an increase in hypertension from tibia Pb content of 8-37 ppm . Although significant fractions of PbB can be attributed to drinking water (Dudi et al, 2005;Triantafyllidou et al, 2007), other sources such as Pb paint, dust, and leaded gas can be the important sources of Pb (ATSDR, 2015).…”
Section: Gowd Andmentioning
confidence: 99%
“…Hu et al (2006) observed an increase in hypertension from tibia Pb content of 8-37 ppm . Although significant fractions of PbB can be attributed to drinking water (Dudi et al, 2005;Triantafyllidou et al, 2007), other sources such as Pb paint, dust, and leaded gas can be the important sources of Pb (ATSDR, 2015).…”
Section: Gowd Andmentioning
confidence: 99%
“…Wang et al (2012) used 0.22 polyethersulfone (PES) syringe filters to separate dissolved lead in lead(IV) oxide formation studies. Dudi et al (2005) specified the use of 0.45-μm nylon syringe filters to quantify soluble lead leached from lead pipes. Studies by Lytle and Schock (2005) and Lytle et al (2009) used 25-mmdiameter 0.2 polypropylene (PP) syringe filters to separate soluble and particulate lead fractions during lead precipitation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst lead pipes are banned for use in many jurisdictions including Hong Kong, there has been increasing concern on the effect of lead-containing solder and pipe fixtures on excess lead concentration in drinking water. Previous studies suggested that the dissolution of Pb-based solder was a significant contributor of lead in drinking water; it is generally recognized that galvanic corrosion plays an important role in the lead release, which depends significantly on the chloride to sulfate concentration of the water. As lead is usually added during the manufacturing of copper alloy fittings for improving machinability and corrosion control, brass fixtures (typically containing 2–8% lead) can also be a potential source of Pb in drinking water. When copper pipes are connected with brass joints, galvanic corrosion can cause elevated Pb in water and the formation of lead particulates and scales on the pipe surface; the effect of sequencing of partially replaced lead pipes on lead leaching has also been studied. , More recently, the importance of particulate lead in drinking water and the effect of flow rate on stimulating particle suspension has received increasing attention. , In particular, it was found that, in pipelines where hydrocerussite is the dominated species, the total lead concentration is primarily dissolved lead under both stagnant and laminar flow conditions …”
Section: Introductionmentioning
confidence: 99%